Réponses

Meilleure réponse !
2014-05-11T21:44:06+02:00
1) ABCD =  (2x+1)^{2}
2) FECD = (2x+1)((2x+1)-(x+3))
             = (2x+1)(x-2)
3) FECD = ABCD-ABFE
              = (2x+1)^{2} -(2x+1)(x+3)
4)                     (2x+1)(x-2) =  (2x+1)^{2} -(2x+1)(x+3)
     2x^{2}-4x+x-2
 = ( 4x^{2} +2x+2x+1) - ( 2x^{2}+6x+x+3 )
        2 x^{2} -3x-2 = ( 4x^{2}+4x+1 ) - ( 2x^{2}+7x+3)
                                         =  4x^{2}+4x+1 - 2x^{2}-7x-3
                                         =  2x^{2}-3x-2
5)                 (2x+1)^{2}=2(2x+1)(x-2)
  4x^{2}+2x+2x+1 = 2( 2x^{2}-4x+x-2 )
       4x^{2}+4x+1 = 2( 2 x^{2} -3x-2)
       4x^{2}+4x+1 = 4x^{2}-6x-4
                                   0   =  -10x-5
        \frac{5}{-10} =x